2007
DOI: 10.1016/s0929-6646(09)60221-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Tuberculosis with Delayed Tuberculosis Infection of Total Knee Arthroplasty

Abstract: Tuberculous prosthetic joint infection is rare. While early diagnosis is critical for treatment, it is usually delayed. Here, we present the case of a 72-year-old patient who underwent total knee arthroplasty for his right knee due to degenerative arthritis 4 years ago. Three years after arthroplasty, pulmonary tuberculosis was found and he hesitated on starting antituberculosis chemotherapy. He suffered from progressive pain and swelling of the right prosthetic knee for 2 months before this admission. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Indeed, this situation is usually considered as a strong indication for revision arthroplasty, either one-or two-stage. However, in six cases of our series and 12 cases in the literature [2,9,22,25,34,41,42,46,49] This study has limitations. Firstly, due to its multicenter retrospective design over a long period of time (20 years), our case series has multiple potential biases: data collection and follow-up were not standardized, and the management probably differed not only from one center to another, but also over time.…”
Section: Accepted Manuscriptmentioning
confidence: 69%
“…Indeed, this situation is usually considered as a strong indication for revision arthroplasty, either one-or two-stage. However, in six cases of our series and 12 cases in the literature [2,9,22,25,34,41,42,46,49] This study has limitations. Firstly, due to its multicenter retrospective design over a long period of time (20 years), our case series has multiple potential biases: data collection and follow-up were not standardized, and the management probably differed not only from one center to another, but also over time.…”
Section: Accepted Manuscriptmentioning
confidence: 69%
“…But granulomas can also represent a reaction to the prosthesis or polyethylene wear debris. Acid-fast stains of the joint fluid are positive in 20-25% of the cases, while cultures are positive in approximately 60 to 80%; histological features are non specific [3,10].…”
Section: Discussionmentioning
confidence: 98%
“…The time from prosthesis implantation to manifestations of infection was variable, ranging from 1 month [9] to 38 years [8]. Patients usually presented with non specific clinical findings of an infected, painful and malfunctioning prosthesis [3,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of the lungs, or a second joint. Wang et al [22] reported on a 72-year-old male patient with a 50-year smoking history who developed a chronic cough and progressive knee pain one year following a TKA. Sputum cultures and knee synovial tissue culture confirmed the diagnosis to be TBPJI and pulmonary tuberculosis infection.…”
Section: Reviewmentioning
confidence: 99%